Aggressive Multifocal Recurrent Fibrosarcoma in an Elderly Patient: A Case Report - Nadhim Askar; Widyanti Soewoto (Open Access Indonesian Journal of Medical Reviews, 2025)
Fibrosarcoma is an uncommon malignant mesenchymal neoplasm originating from fibroblasts, notorious for its aggressive clinical behavior, high local recurrence rates, and potential for distant metastatic spread. Managing fibrosarcoma in elderly patients presents unique challenges, particularly when characterized by multifocal and recurrent disease. This case report aims to describe an unusual and particularly challenging presentation of aggressive, multifocal recurrent fibrosarcoma in a 65-year-old female patient. A 65-year-old Indonesian female presented with a complex history of multiple recurrent fibrosarcomas. Her oncological journey began with an inguinal mass excised in 2022, diagnosed as Grade I fibrosarcoma, followed by chemotherapy. Despite these interventions, she experienced recurrence at the primary site and developed new masses in the abdomen, flank, gluteal regions, left breast, right supraclavicular area, right antebrachial region, and left femur over the ensuing year. Comprehensive imaging, including whole abdomen MSCT, revealed multiple widespread soft tissue masses with suspicious lymphadenopathy and equivocal liver lesions. Histopathological examination of subsequent biopsies and excised specimens, supported by immunohistochemistry (CD34 positive; S-100, CD-117, Desmin negative), consistently confirmed recurrent fibrosarcoma. The patient underwent multiple extensive wide excision surgeries for various tumor locations, including the left inguinal region, left breast, left flank, bilateral gluteal regions, left antebrachial, and left supraclavicular areas. In conclusion, this case underscores the exceptionally aggressive and relentless nature of multifocal recurrent fibrosarcoma in an elderly individual. Despite an initial low-grade diagnosis and adjuvant chemotherapy, the disease progressed rapidly with widespread recurrences. Aggressive surgical management with wide excision remains the cornerstone of treatment in an attempt to achieve local control. However, the propensity for new lesions highlights the limitations of current therapies for such extensive disease. Vigilant, long-term surveillance and a multidisciplinary approach are paramount. This case also emphasizes the need for further research into the molecular drivers of such aggressive behavior and the development of more effective systemic therapies.